Starting with the left side of the equation:
-2(7x - 1)
= -14x + 2
And the right side of the equation:
-7(-5x + 8)
= 35x - 56
Therefore, the simplified equation is:
-14x + 2 = 35x - 56
Rearranging the equation to solve for x:
-14x - 35x = -56 - 2
-49x = -58
x = 58/49
So, the solution for x is around: x = 1.1837
Solve the following equation for xx. Express your answer in the simplest form.
minus, 2, left parenthesis, 7, x, minus, 1, right parenthesis, equals, minus, 7, left parenthesis, minus, 5, x, plus, 8, right parenthesis
−2(7x−1)=
−7(−5x+8)
1 answer